2012
DOI: 10.1186/1472-6920-12-64
|View full text |Cite
|
Sign up to set email alerts
|

A new paradigm for teaching behavior change: Implications for residency training in family medicine and psychiatry

Abstract: BackgroundPrimary care physicians (PCPs) provide ~50 % of all mental health services in the U.S. Given the widening gap between patient mental health needs and resources available to meet those needs, there is an increasing demand for family medicine and psychiatry trainees to master competencies in both behavioral medicine and primary care counseling during residency-if for no other reason than to accommodate the realities of medical practice given the oft present gap between the need for psychiatric services… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
25
2
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(28 citation statements)
references
References 22 publications
0
25
2
1
Order By: Relevance
“…A few studies reported a discrete intervention, such as a single workshop, 18,22,23 whereas others described more intensive MI interventions, including multiple sessions within a communication curriculum, 20 a dedicated MI rotation, 17 and a longitudinal MI curriculum. 16 Content of the interventions was mixed.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…A few studies reported a discrete intervention, such as a single workshop, 18,22,23 whereas others described more intensive MI interventions, including multiple sessions within a communication curriculum, 20 a dedicated MI rotation, 17 and a longitudinal MI curriculum. 16 Content of the interventions was mixed.…”
Section: Resultsmentioning
confidence: 99%
“…[16][17][18][19][20][21][22][23][24] T A B L E 1 displays details extracted from the studies, and T A B L E 2 includes strengths and limitations of the studies. Five studies were preintervention and postintervention studies, 3 were postintervention studies, and 1 study was a randomized controlled trial.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations